2014
DOI: 10.1186/preaccept-2051958771459391
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signatures of near-extinction and rebirth of the crested ibis and other endangered bird species

Abstract: Background: Nearly one-quarter of all avian species is either threatened or nearly threatened. Of these, 73 species are currently being rescued from going extinct in wildlife sanctuaries. One of the previously most critically-endangered is the crested ibis, Nipponia nippon. Once widespread across North-East Asia, by 1981 only seven individuals from two breeding pairs remained in the wild. The recovering crested ibis populations thus provide an excellent example for conservation genomics since every individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 47 publications
3
55
1
Order By: Relevance
“…Although the genome-wide level of heterozygosity in the Paradise Parrot genome is not as high as in the abundant Australian Budgerigar, it is almost twice as high as in the now endangered New Zealand Kea (Table 2). It is also higher than the genome-wide level of heterozygosity found in almost all endangered and vulnerable species listed by [47]. It is within the range of what is found for species falling in the IUCN category "least concerned".…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Although the genome-wide level of heterozygosity in the Paradise Parrot genome is not as high as in the abundant Australian Budgerigar, it is almost twice as high as in the now endangered New Zealand Kea (Table 2). It is also higher than the genome-wide level of heterozygosity found in almost all endangered and vulnerable species listed by [47]. It is within the range of what is found for species falling in the IUCN category "least concerned".…”
Section: Discussionmentioning
confidence: 54%
“…Li et al [47] found that threatened species, of which some had gone through severe population bottlenecks, on average had considerably lower genome-wide levels of heterozygosity than common and abundant species. Although the genome-wide level of heterozygosity in the Paradise Parrot genome is not as high as in the abundant Australian Budgerigar, it is almost twice as high as in the now endangered New Zealand Kea (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of molecular genetic diversity found in this study are consistent with a depleted diversity compared to other passerine species (Figure 1). Comparison of individual heterozygosity in pairs of threatened and non-threatened bird species [15] similarly showed a diversity roughly two to five times lower in threatened birds. Our average level of individual heterozygosity (0.00069; see Figure S1) falls well within the range observed by [15] for threatened bird species (0.0004-0.00091).…”
Section: Lack Of Adaptive Potential In the Hihi In Comparison To Othementioning
confidence: 95%
“…Furthermore, birds in the orders Gaviiformes and Ciconiiformes have been affected by changes in land use and degradation of freshwater systems because of their high dependence on aquatic habitats (Arzel et al, 2015), vulnerability to pathogens (Silva et al, 2010), and exposure to pollutants derived from aquatic contamination (Fontenelle, 2006). There are strong examples in the literature suggesting that populations of many Ciconiiformes have undergone genetic bottlenecks as evidenced by the loss of genetic diversity and an increase in deleterious mutations (Li et al, 2014) due to inbreeding, climate change, habitat loss, hunting and environmental pollution, especially by agrochemicals (e.g., Zhang et al, 2004;Miño et al, 2009). Significant correlations were observed between the number of loci used and the estimates of H O and H E .…”
Section: Genetic Diversity Ecological Attributes and Conservaion Statusmentioning
confidence: 98%